Influence of the sample geometry on critical current density of high Tc granular superconductors - D’ Ovidio, Claudio A.; Fiscina, Jorge E.; Esparza, Daniel Antonio (Comisión Nacional de Energía Atómica; Argentina)
Fil: D’ Ovidio, Claudio A. Comisión Nacional de Energía Atómica; Argentina